Effect of aerobic pre-treatment on production of hydrolases and volatile fatty acids during anaerobic digestion of solid sisal leaf decortications residues (International Journal of Medicine and Medical Sciences, 2020)
The effect of aerobic pretreatment on the production of hydrolases and volatile fatty acids during anaerobic digestion of solid sisal decortications leaf residue (SLDR) was investigated. Batch solid waste bioreactors with working volume of 2 litres were used in this study. Batch loads of aerobically treated or untreated sisal leaf residue inoculated with activated sludge mixed culture were packed into the bioreactors and operated anaerobically for 400 h. The fermentation products were mainly (mg/g total volatile fatty acids, VFAs): acetic acid (287), n-butyric acid (201), n-valeric acid (96) and caproic acid (62) as well as with low amounts of propionic acid and iso-butyric acid for aerobic pre-treated sisal leaf waste solids. Contrarily, for the untreated system, the fermentation products were chiefly (mg/g total volatile fatty acids): propionic acid (317), isobutyric acid (276), n-butyric acid (96), acetic acid (84) and insignificant amounts of n-valeric acid, iso-valeric acid and caproic acid. Although the activities of hydrolytic enzymes found were similar for both treated and untreated SLDR, proportions of VFAs obtained with the former residues appeared to be better substrates for biomethanantion than those obtained from the latter substrates. These results indicated the potential of aerobic pre- treatment for enhanced bioconversion of SLDR. The present study, reports for the first time the types and levels of VFAs and hydrolases produced during anaerobic digestion of aerobic pre-treated SLDR and could be used as a basis for designing a pilot scale process.